Clinical profile of congenital limb anomalies in neonates - Parikh, Yogesh N.; Kalathia, Mitul B.; Soodhana, Dhanya (International Journal of Contemporary Pediatrics, 2018)
Background: Reported birth prevalence of congenital limb defects vary from country to country. Epidemiological studies permit the timely detection of trends in congenital limb anomalies and the associations with other birth defects. The objective of this study was to know the prevalence and the variety of congenital limb anomalies and their association with other anomalies. Methods: A prospective observational study in which all newborns reported to the neonatal department were surveyed to find out the incidence, diversity and association of limb anomalies. Age of the mother, risk factors and other demographic data of the newborns was analyzed. Babies born less than 28 weeks were excluded from the study. Results: The prevalence was 6.34 per thousand live births. The majority of the neonates were term babies and female. 28 % of the babies were born out of consanguineous marriage. The mean age of the mother was 25. Median parity was 1. 9.52 % of the babies had a history of anomaly in the sibling. 4.76 % had a history of still birth. The most common congenital anomaly was congenital talipo equino varus. The other congenital limb anomalies observed were polydactyly, syndactyly, bifid thumb and absence of the radius. There were multiple congenital anomalies in 28.57 % of the babies. Conclusions: The study has given us an insight into the variety of congenital limb malformations and also into the possible etiological factors. A study done on a larger population would probably help us assess the incidence and pattern of occurrence of limb anomalies and help us counsel the parents.